2023
DOI: 10.3390/ani13203192
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study and Identification of Candidate Genes for Intramuscular Fat Fatty Acid Composition in Ningxiang Pigs

Qinghua Zeng,
Hu Gao,
Shishu Yin
et al.

Abstract: Ningxiang pigs exhibit a diverse array of fatty acids, making them an intriguing model for exploring the genetic underpinnings of fatty acid metabolism. We conducted a genome-wide association study using a dataset comprising 50,697 single-nucleotide polymorphisms (SNPs) and samples from over 600 Ningxiang pigs. Our investigation yielded novel candidate genes linked to five saturated fatty acids (SFAs), four monounsaturated fatty acids (MUFAs), and five polyunsaturated fatty acids (PUFAs). Significant associati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Moreover, PRKG1 knockout mice have decreased triglyceride stores in brown adipose tissue [41]. In pigs, a GWAS on fatty acid composition in 691 Ningxiang pigs revealed that PRKG1 was associated with saturated fatty acid traits [42]. According to RNA-Seq analysis, PRKG1 exhibits differential expression between high and low fatty acid composition groups in the muscle [43].…”
Section: Patterns Of Selection Signaturesmentioning
confidence: 99%
“…Moreover, PRKG1 knockout mice have decreased triglyceride stores in brown adipose tissue [41]. In pigs, a GWAS on fatty acid composition in 691 Ningxiang pigs revealed that PRKG1 was associated with saturated fatty acid traits [42]. According to RNA-Seq analysis, PRKG1 exhibits differential expression between high and low fatty acid composition groups in the muscle [43].…”
Section: Patterns Of Selection Signaturesmentioning
confidence: 99%